1990
DOI: 10.1002/dev.420230802
|View full text |Cite
|
Sign up to set email alerts
|

Development of coordinated movement in chicks: I. Temporal analysis of hindlimb muscle synergies at embryonic days 9 and 10

Abstract: In this study, we examined electromyographic activity for an ensemble of hindlimb muscles during spontaneous activity in chick embryos to advance understanding of early motor coordination and its relationship to later emerging behaviors. Four-channel recordings were obtained from 6 muscles in ovo at embryonic Days 9 and 10. Analyses indicated that when muscles are repetitively active, patterns during embryonic motility are distinct from those for other behaviors. For example, unlike the muscle patterns for loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 30 publications
(50 reference statements)
6
37
0
Order By: Relevance
“…3C). Leg muscles participate in ensembles of agonist and antagonist activity during motility as early as E9 but at slower rhythms of 0.2-2 Hz (Bradley and Bekoff 1990;Landmesser and O'Donovan 1984). There is considerable evidence that these slow rhythms in younger embryos are governed by a spinal recurrent excitatory network and synaptic fatigue (Chub and O'Donovan 1998;O'Donovan and Chub 1997;Tabak et al 2000).…”
Section: Age-related Changes In Rlmsmentioning
confidence: 99%
See 1 more Smart Citation
“…3C). Leg muscles participate in ensembles of agonist and antagonist activity during motility as early as E9 but at slower rhythms of 0.2-2 Hz (Bradley and Bekoff 1990;Landmesser and O'Donovan 1984). There is considerable evidence that these slow rhythms in younger embryos are governed by a spinal recurrent excitatory network and synaptic fatigue (Chub and O'Donovan 1998;O'Donovan and Chub 1997;Tabak et al 2000).…”
Section: Age-related Changes In Rlmsmentioning
confidence: 99%
“…Throughout most of development, movements look random, jerky and small in amplitude, a pattern also referred to as type I motility (Hamburger and Oppenheim 1967). Yet by E9, leg movements are produced by alternating flexor/extensor muscle activity and coupled joint rotations at the hip, knee, and ankle at frequencies of 0.2-2 Hz (Bekoff 1976;Bradley and Bekoff 1990;Chambers et al 1995). The muscle patterns and coupled rotations of hip and knee persist up through hatching, suggesting they are controlled by a pattern generating network (Bekoff 1976(Bekoff , 1992Bradley 1999Bradley , 2001Bradley et al 2005;Sharp et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In future studies, it should be equally possible to inhibit neuronal activity in peripheral axons using light-driven chloride or proton pumps (Arrenberg et al 2009;Chow et al 2010). Importantly, we have shown that tonic activation of motor neurons innervating flexor muscles can disrupt normal extension of the leg.…”
Section: Discussionmentioning
confidence: 99%
“…Since embryonic motility has been well-described on E9 (Bradley and Bekoff 1990;Sharp et al 1999;Sharp and Bekoff 2001), we chose to examine light-evoked movement more carefully at this age. Brief (ϳ1-s) pulses of light centered over the thigh and presented between episodes of spontaneous movement produced flexions of the leg that were very reproducible when presented with a period Ͼ0.5 Hz.…”
Section: Embryonic Movement Evoked By Chief Activationmentioning
confidence: 99%
“…1999) and muscle discharge (Bekoff et al 1975;Bradley and Bekoff 1990;Ryu and Bradley 2009) have been accomplished in acute preparation of freely moving chicken embryos across much of embryogenesis. These types of studies have given rise to a description of how motor activity is altered during development (Bekoff 2001;Bradley 2001;Sharp and Bekoff 2001), but still lacking is an understanding of the relationship of muscle activity to force production by the limb and how this may be regulated by sensory feedback.…”
mentioning
confidence: 99%